Possibilities at the Formative Stage of the Vernacular Chinese Novel: A Study of San Sui pingyao zhuan 三遂平妖傳 (Three Sui Quelling the Demon’s Revolt) - Jin, Huan (JAOS, 2024)
This study centers on a valuable specimen of the early vernacular Chinese novel, San Sui pingyao zhuan, to explore dynamic possibilities at the formative stage of the Chinese novel. Close inspection of the physical aspects of the extant edition of the work suggests it is a reprint bearing traces of multiple earlier editions. The analysis of the obscure chuanqi play Si xi ji shows that the story tradition of "Three Sui quelling the rebels" already existed in the mid-sixteenth century. San Sui pingyao zhuan shares much common ground with early zaju drama, fifteenth-century cihua (chantefables), and pinghua (historical novels). Linking this novel with other early examples of popular literature that preceded or were contemporaneous with it, my study deepens our understanding of the formation of the early vernacular novel as well as the world of popular literature in which the novel was situated.